RESPONS PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) TERHADAP PEMBERIAN ABU BOILER DAN PUPUK UREA PADA MEDIA PEMBIBITAN - Uli Kris Putri Sitorus; Balonggu Siagian; Nini Rahmawati (Jurnal Agroekoteknologi, 2014)
Growing media fertility can be improved or enhanced with inorganic or organic fertilizer, such asboiler ash, which is one type of solid waste by-product of palm oil mills as well as the source ofnitrogen urea fertilizer, is expected to boost growth of cocoa seedling in the nursery. This researchhad been conducted at experimental field of Fakultas Pertanian USU in May 2013 until September2013, using factorial randomized block design with two factor. The first factor was dose of boiler ash(0, 100, 10 g/polybag) and the second factor was dose of urea fertilizer (0, 5, and 10 g/polybag).Parameter observed were plant height, total of leaf area, dry shoot weight and dry root weight.Theresult showed response of boiler ash on cocoa seed significantly increase total of leaf area and dryshoot weight. Urea fertilizer significantly affect dry shoot weight. Interaction of both significantlyaffect dry shoot weight. The best results from interaction boiler ash and urea fertilizer were obtainedin the treatment of boiler ash at 300 g/polybag and urea fertilizer 5 g/polybag.________________________________________________________________________________Keywords: Boiler Ash, Urea Fertilizer, Cocoa Seed